Identifying determinants of under-5 mortality in Bangladesh: A machine learning approach with BDHS 2022 data - Shayla Naznin; Md Jamal Uddin; Ahmad Kabir (PLoS ONE, 2025)
Background Under-5 mortality in Bangladesh remains a critical indicator of public health and socio-economic development. Traditional methods often struggle to capture the complex, non-linear relationships influencing under-5 mortality. This study leverages advanced machine learning models to more accurately predict under-5 mortality and its key determinants. By enhancing prediction accuracy, the study aims to provide actionable insights for improving child survival outcomes in Bangladesh. Methods Multiple machine learning (ML) algorithms were applied to data from the 2022 Bangladesh Demographic Health Survey, including Random Forest, Decision Tree, K-Nearest Neighbors, Logistic Regression, Support Vector Machine, XGBoost, LightGBM and Neural Networks. Feature selection was performed using the Boruta algorithm and model performance was evaluated by comparing accuracy, precision, recall, F1 score, MCC, Cohen’s Kappa and AUROC. Results The Random Forest (RF) model emerged as the most effective predictive model for under-5 mortality in Bangladesh, surpassing other models in various performance metrics. The RF model delivered impressive results, achieving 98.75% Accuracy, 98.61% Recall, 98.88% Precision, 98.74% F1 Score, 97.5% MCC, 97.5% Cohen’s Kappa and an AUROC of 99.79%. These metrics highlight its exceptional predictive accuracy and robustness. Key factors influencing under-5 mortality identified by the model included the number of household members, wealth index, parents’ education (both father’s and mother’s), the number of antenatal care (ANC) visits, birth order and the father’s occupation. Conclusions The Random Forest model excelled in predicting under-5 mortality in Bangladesh identifying key predictors such as household size, wealth, parental education, ANC visits, birth order and father’s occupation. These findings underscore the efficacy of machine learning in predicting under-5 mortality and identifying critical determinants these also provide a data-driven foundation for policymakers to design targeted interventions, such as improving access to maternal healthcare, promoting parental education and addressing socio-economic inequalities, ultimately contributing to enhanced child survival outcomes in Bangladesh.